Application of the curriculum 2013 in accounting learning for vocational school - Neta Dian Lestari; Reva Maria Valianti; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The quality of education is reflected through the personality, knowledge and skills and skills possessed by students, a manifestation of the implementation of the curriculum 2013 in learning. The purpose of the study is to analyze the implementation of the curriculum 2013 in the form of planning, implementation and assessment in accounting learning at private vocational schools in Palembang City. The population of this study is a private vocational school in the city of Palembang. While the research sample is a sample with a purpose, as many as 12 private vocational schools each with 2 (two) teachers, as respondents where the school concerned has a major in Accounting and Institutional Finance and is accredited A. The sources of data collected are in the form of primary data, namely observations and questionnaires. Methods or data analysis using descriptive analysis. The results of the research are the implementation of the Curriculum 2013 in private vocational schools in Palembang City and the role of educators in the implementation of the curriculum 2013 in terms of the aspect of learning planning that is